We, the People of Europe? : Reflections on Transnational Citizenship - Balibar, Etienne, 1942- (Translation/transnation., 2014)
Étienne Balibar has been one of Europe's most important philosophical and political thinkers since the 1960s. His work has been vastly influential on both sides of the Atlantic throughout the humanities and the social sciences. In We, the People of Europe?, he expands on themes raised in his previous works to offer a trenchant and eloquently written analysis of "transnational citizenship" from the perspective of contemporary Europe. Balibar moves deftly from state theory, national sovereignty, and debates on multiculturalism and European racism, toward imagining a more democratic and less state-centered European citizenship. Although European unification has progressively divorced the concepts of citizenship and nationhood, this process has met with formidable obstacles. While Balibar seeks a deep understanding of this critical conjuncture, he goes beyond theoretical issues. For example, he examines the emergence, alongside the formal aspects of European citizenship, of a "European apartheid," or the reduplication of external borders in the form of "internal borders" nurtured by dubious notions of national and racial identity. He argues for the democratization of how immigrants and minorities in general are treated by the modern democratic state, and the need to reinvent what it means to be a citizen in an increasingly multicultural, diversified world. A major new work by a renowned theorist, We, the People of Europe? offers a far-reaching alternative to the usual framing of multicultural debates in the United States while also engaging with these debates.